CMC: A consensus multi-view clustering model for predicting Alzheimer's disease progression. (February 2021) - Zhang, Xiaobo; Yang, Yan; Li, Tianrui; Zhang, Yiling; Wang, Hao; Fujita, Hamido
Highlights: A novel consensus multi-view clustering model via non-negative matrix factorization has been proposed to predict Alzheimer's disease progression. Multiple brain MRI views datasets were constructed using SIFT, KAZE and Gabor filter technologies. Demonstrating that the proposed method achieves superior performance. Providing a new solution to the medical examination and prevention of Alzheimer's disease progression. Abstract: Machine learning has been used in the past for the auxiliary diagnosis of Alzheimer's Disease (AD). However, most existing technologies only explore single-view data, require manual parameter setting and focus on two-class (i.e., dementia or not) classification problems. Unlike single-view data, multi-view data provide more powerful feature representation capability. Learning with multi-view data is referred to as multi-view learning, which has received certain attention in recent years. In this paper, we propose a new multi-view clustering model called Consensus Multi-view Clustering (CMC) based on nonnegative matrix factorization for predicting the multiple stages of AD progression. The proposed CMC performs multi-view learning idea to fully capture data features with limited medical images, approaches similarity relations between different entities, addresses the shortcoming from multi-view fusion that requires manual setting parameters, and further acquires a consensus representation containing shared features and complementary knowledge of multiple view data. It not only can improve the predication performance of AD, but also can screen and classify the symptoms of different AD's phases. Experimental results using data with twelve views constructed by brain Magnetic Resonance Imaging (MRI) database from Alzheimer's Disease Neuroimaging Initiative expound and prove the effectiveness of the proposed model.